2019
DOI: 10.1371/journal.pone.0212226
|View full text |Cite
|
Sign up to set email alerts
|

Ideating iDNA: Lessons and limitations from leeches in legacy collections

Abstract: Indirect methods for conducting faunal inventories present great promise, and genomic inventories derived from environmental sources (eDNA) are improving. Invertebrate ingested DNA (iDNA) from terrestrial leeches in the family Haemadipsidae has shown potential for surveying vertebrates and biodiversity monitoring in protected areas. Here we present an initial, and critical, evaluation of the limitations and biases of current iDNA protocols for biodiversity monitoring using both standard and NGS barcoding appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…In both leech species, the gut microbial communities are dominated by Aeromonas, Bacteroidales, and Clostridiales species. This is consistent with previous findings that Bacteroidetes and Aeromonas are common but not obligate in the gut of animals and insects fed on blood (46-51). Siddall et al have shown that many sanguivorous leeches maintain a gut symbiosis with Aeromonas and Bacteroidetes species (8).…”
Section: Discussionsupporting
confidence: 93%
“…In both leech species, the gut microbial communities are dominated by Aeromonas, Bacteroidales, and Clostridiales species. This is consistent with previous findings that Bacteroidetes and Aeromonas are common but not obligate in the gut of animals and insects fed on blood (46-51). Siddall et al have shown that many sanguivorous leeches maintain a gut symbiosis with Aeromonas and Bacteroidetes species (8).…”
Section: Discussionsupporting
confidence: 93%
“…with previous findings that Bacteroidetes and Aeromonas are commonly (but not universally) found in the gut of animals and insects fed on blood (43)(44)(45)(46)(47)(48). Siddall et al showed that many sanguivorous leeches maintain a gut symbiosis with Aeromonas and Bacteroidetes species (10), and we therefore hypothesize that the conserved taxonomic orders have been evolutionarily maintained in hirudinid leeches despite host species diversification and geographic separation.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, a universal primer set targeting a partial fragment of the COI barcode region (mlCOIintF/jgHCO2198) (Leray et al, 2013 ; Geller et al, 2013 ) was chosen to allow detection of diet across a broad taxonomic range of metazoans (Leray et al, 2013 ). In addition, this primer set can also provide information about possible metazoan endoparasites (Bohmann et al, 2018 ) and can simultaneously coamplify leech DNA, thereby providing DNA barcode‐based host identification; another study using multiple primer sets have also detected vertebrate, parasite and bacterial DNA (Siddall et al, 2019 ). Nevertheless, this coamplification can cause lower detection rates of the diet, as the leech DNA can overpower the diet DNA in the leech gut contents.…”
Section: Discussionmentioning
confidence: 99%
“…For terrestrial leeches (including members of the families Xerobdellidae, Cylicobdellidae, Americobdellidae and Haemopidae), detailed information is also lacking; for example, the diet of the Mexican terrestrial leech Diestecostoma mexicana (Baird, 1869) is still completely unknown. The major exception to this is the family Haemadipsidae, for which the diet is relatively well understood through studies on invertebrate‐derived DNA, or iDNA, which aim to monitor vertebrates through DNA detection in leech bloodmeals (Drinkwater et al, 2020 ; Fahmy et al, 2019 , 2020 ; Schnell et al, 2012 , 2018 ; Nguyen et al, 2021 ; Siddall et al, 2019 ; Tessler et al, 2018 ; Weiskopf et al, 2018 ). As such, the dearth of data extends across the leech phylogeny, rather than being explicit to certain taxa.…”
Section: Introductionmentioning
confidence: 99%